Work incentives at the extensive and intensive margin in Europe: The role of taxes, benefits and population characteristics - H. Xavier Jara; Katrin Gasior; Mattia Makovec (University of Essex, Institute for Social and Economic Research (ISER), 2019)
Tax and benefit systems play an important role in determining work incentives at both, the extensive and the intensive margin of labour supply. The aim of this paper is to provide a comprehensive comparative analysis of work incentives in the EU. Our analysis makes use of microsimulation techniques and representative household surveys from all 28 EU countries to compare the distribution of short- and long-term participation tax rates and marginal effective tax rates across population subgroups. We focus on people currently in work and characterise the population facing low work incentives in each country. Our results highlight the large variation in the distribution of work incentives across EU countries, explained not only by differences in the design of tax-benefit systems, but also by the characteristics of the labour force across countries. Unemployment insurance benefits contribute substantially to short-term participation tax rates and explain on average 20 percentage point difference between work incentives of short- vs. long-term unemployment. Our analysis further highlights the need to use microdata to study differences across countries in terms of the population subgroups facing low incentives to work with the aim to inform the policy debate on potential reforms to make work pay.
Keywords: H31; E60; 330; work incentives; extensive margin; intensive margin; social policy